ANALYSIS OF PHILOSOPHICAL, SOCIOLOGICAL AND JURIDICAL BASIS PROTECTION OF CIVIL RIGHTS CHILDREN BORN OUTSIDE OF MARRIAGE IN INDONESIA - Ahmad Baihaki; Dini Dewi Heniarti (Adisam Publisher, 2025)
The issue of protecting children born outside of marriage is still a crucial legal problem in the legal system in Indonesia. This research aims to identify the philosophical, sociological, and juridical foundations for protecting the civil rights of children born outside of marriage and how Islamic law uses the principles of maqashid al-syariah to provide a comprehensive legal solution to increase legal protection efforts for the civil rights of children born outside of marriage. This research uses normative legal research methods and analyzes the legal problems of this research from the perspective of maqashid al-syariah. The findings show that the protection of the civil rights of children born outside of marriage does not yet have a strong philosophical, sociological, and juridical basis. As one of the legal systems in the legal system in Indonesia, Islamic law regulates that the absence of a birth relationship between children born outside of marriage and their biological father is a form of justice in maintaining the honor and sanctity of every child born. The negative stigma towards children born outside of marriage is only a domino effect from the view of society which considers the act of adultery committed by both parents as a depraved and vile act. Even though children born outside of marriage are not related by birth, their biological father still has a legal obligation to provide support and inheritance through a will or mandatory testament as a form of ta’zir punishment. This is following the principles of Maqashid al-Syariah to maintain religion (hifz al-din), soul (hifz al-nafs), and descendants (hifz al-nasl).